Low-Complexity Instantaneous Ambiguity Resolution with the Affine-Constrained GNSS Attitude Model - Giorgi, G.; Teunissen, Peter (Institute of Electrical and Electronics Engineers, 2013)
In this contribution a new approach to ambiguity resolution for Global Navigation Satellite System (GNSS)-based attitude estimation applications is discussed and tested. This approach enhances the observation model by means of additional linear constraints. These constraints are implicitly derived by applying an affine transformation to the unknown real-valued parameters, and largely aid the integer ambiguity estimation through an improved float estimation. The new method is characterized by a lower computational complexity than a rigorous nonlinearly-constrained GNSS attitude model, and at the same time it guarantees higher performance than unconstrained, and therefore weaker, models. The ambiguity resolution performance of the affine-constrained approach is tested through a series of simulated as well as actual data sets, demonstrating the validity and usefulness of the proposed approach for multi-antenna GNSS-based attitude determination applications.